Aplicación de la técnica de frenkel para control de equilibrio y coordinación en el síndrome de caída del adulto mayor del centro diurno del buen vivir – fundación para el desarrollo integral comunitario más vida ( fudeinco) - Marisol Cristina, Molina Maygualema (2017)
APPLICATION OF THE FRENKEL TECHNIQUE FOR BALANCE CONTROL AND COORDINATION IN FALL SYNDROME OF THE SENIOR ADULT FROM FUNDACION PARA EL DESAROLLO INTEGRAL COMUNITARIO MÁS VIDA (FUDEINCO) ABSTRACT: In this research is applied in older adults of the "FUNDACION PARA EL DESAROLLO INTEGRAL COMUNITARIO MAS VIDA FUDEINCO", the Frenkel exercises are a series of exercises that will attempt to improve proprioceptive control of the limbs. Frenkel They are a series of exercises that go from the accomplishment of very simple exercises, that is to say, without influence of the gravity or without involving many segments; And they are going to evolve to movements or exercises much more complex. Exercises can be made difficult by increasing the influence of gravity, including more and more body segments, varying the pace either by increasing speed or by slowing down or even stopping in the middle of an exercise, limiting vision, Patient when making the movements. It is essential to emphasize the posture and movements that interest us most within the globality of the patient. Once the patient has achieved a simple movement he / she will move to a more difficult degree, after he / she has mastered the simple exercise it is important to continue his / her training at home, requesting him to repeat it every three or four hours. This way you will get it, or we will try to automate it. Normally, within each session to not fatigue the patient usually do four repetitions of the movement. With the application of the Frenkel exercise routine to improve the balance and coordination of the older adult decreasing the risk of suffering from the fall syndrome.